Bronchogenic Carcinoma: Some Aspects of its Aetiology and Prevention (Res Medica, 2013)
Fifty years ago, bronchogenic carcinoma was a rare disease; to-day it is the most frequently encountered intra-thoracic neoplasm and it is one of the commonest of all the killing tumours. It still bears a grave prognosis despite the advances in surgical and diagnostic technique which allow the treatment to be begun much earlier than was possible in former days. The general public, let alone the medical profession, is becoming increasingly alarmed by this condition, not only on account of its lethal character, but because of the correlation between it and the almost universal habit of cigarette smoking. Questions of ethics and sociology, of politics and economics, of industry and international relations are some of the problems closely interwoven in the suspected aetiology and in the hoped-for prevention of bronchogenic carcinoma.